+0  
 
0
65
1
avatar

https://vle.mathswatch.co.uk/images/questions/question18411.png

please

 Mar 26, 2020
 #1
avatar+20768 
0

v2  =  u2 + 2·a·s          u = 12     a = -6     s = 9

 

Substituting:     v2  =  u2 + 2·a·s      --->     v2  =  (12)2 + 2(-6)(9)     <---     finish

 

Solve     v2  =  u2 + 2·a·s   for s:

 

  u2 + 2·a·s  =  v2

            2as  =  v2 - u2               (subtract u2 from both sides)

                s  =  (v2 - u2) / (2a)   (divide both sides by 2a)       

 Mar 26, 2020

36 Online Users

avatar
avatar
avatar